2018
DOI: 10.1186/s13104-018-3631-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of recreational drug use among medical and nursing students in Cameroon: a cross sectional analysis

Abstract: ObjectiveMedical and nursing students in Cameroon are likely to have mental health problems given the stressful nature of their studies. Paucity of mental health institutions in the country implies they hardly get access to professional help when needed and are obliged to develop coping strategies such as recreational drug use. This study aims to determine the prevalence and predictors of recreational drug use among a group of Cameroonian medical and nursing students.ResultsCross-sectional analysis of 852 medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 22 publications
(26 reference statements)
4
29
2
2
Order By: Relevance
“…In the UK, research across seven universities, using the same questionnaire as in the current study, reported that regular IDU was significantly more likely among students with heavy episodic drinking or possible alcohol dependency [ 28 ]. Our findings support others where there was positive associations between heavy-drinking behaviour and ISU [ 33 , 107 ]; alcohol consumption was an independent predictor of recreational drug use among medical and nursing students in Cameroon (OR 5.08; 95% CI 1.54–16.73; P = 0.008) [ 108 ]; frequency of alcohol use predicted illicit drug experience among college students in Turkey [ 109 ]; and alcohol use was associated with ever IDU [ 102 ].…”
Section: Discussionsupporting
confidence: 90%
“…In the UK, research across seven universities, using the same questionnaire as in the current study, reported that regular IDU was significantly more likely among students with heavy episodic drinking or possible alcohol dependency [ 28 ]. Our findings support others where there was positive associations between heavy-drinking behaviour and ISU [ 33 , 107 ]; alcohol consumption was an independent predictor of recreational drug use among medical and nursing students in Cameroon (OR 5.08; 95% CI 1.54–16.73; P = 0.008) [ 108 ]; frequency of alcohol use predicted illicit drug experience among college students in Turkey [ 109 ]; and alcohol use was associated with ever IDU [ 102 ].…”
Section: Discussionsupporting
confidence: 90%
“…The proportion of study participants who completed all the three doses in this study is slightly higher than the finding from an institutional-based cross-sectional study in Ethiopia conducted among 423 respondents [ 9 ] who noted that 16.1% of the respondents had ever received HBV vaccination and 12.9% of the health workers had received all the three doses of HBV. Mbanga et al [ 10 ], in another study conducted in Cameroon that recruited 714 respondents, also found that 6.81% had attained complete vaccination against HBV.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a cross-section study conducted in South Africa among 400 respondents [ 11 ] also found that 55.7% of HCWs had received at least one dose of HBV vaccine, and 53 (15.4%) were fully vaccinated having received all the three doses of HB vaccine as recommended by the World Health Organization (WHO). Mbanga et al [ 10 ] conducted a cross-sectional study in Cameroon among 714 respondents; they established that poor HBV vaccination uptake was attributed to worries and fear of side effects, as well as fear of being infected by the vaccine. This study among HCWs in South Sudan found that slightly more than half of the respondents accepted that they were at risk of HBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Recreational drug use was also found to be independently associated with burnout syndrome, with students who used recreational drugs like marijuana and tramadol having higher burnout scores on the OLBI burnout scale. This is a unique and interesting finding, but it is uncertain whether recreational drug use directly results in students becoming more burned out or if students who are already underperforming and are experiencing high levels of stress turn to recreational drug use as a source of comfort [32]. This association has to be explored more in prospective study designs.…”
Section: Discussionmentioning
confidence: 99%